Research on Rising Pantograph Surge overVoltage for High-speed EMUs - NIEYing; HU Xue-yong (机车电传动)
Based on structure of high-speed EMUs body, equivalent electric circuit model was established to analyze the transmitting and reflecting characteristics between different car bodies, as well as experiments were carried out in field. It was demonstrated that wave figure of theoretic result was consistent with experimental result but difference for over-voltage amplitude, reasons of which were analyzed.